The dynamics of very high Alfvén Mach number shocks in space plasmas - Sundberg,T; Burgess,D; Scholer,M; Masters,A; Sulaiman,AH (Astrophysical Journal Letters, 2017)
Astrophysical shocks, such as planetary bow shocks or supernova remnant shocks, are often in the high or very-high Mach number regime, and the structure of such shocks is crucial for understanding particle acceleration and plasma heating, as well inherently interesting. Recent magnetic field observations at Saturn's bow shock, for Alfvén Mach numbers greater than about 25, have provided evidence for periodic non-stationarity, although the details of the ion- and electron-scale processes remain unclear due to limited plasma data. High-resolution, multi-spacecraft data are available for the terrestrial bow shock, but here the very high Mach number regime is only attained on extremely rare occasions. Here we present magnetic field and particle data from three such quasi-perpendicular shock crossings observed by the four-spacecraft Cluster mission. Although both ion reflection and the shock profile are modulated at the upstream ion gyroperiod timescale, the dominant wave growth in the foot takes place at sub-proton length scales and is consistent with being driven by the ion Weibel instability. The observed large-scale behavior depends strongly on cross-scale coupling between ion and electron processes, with ion reflection never fully suppressed, and this suggests a model of the shock dynamics that is in conflict with previous models of non-stationarity. Thus, the observations offer insight into the conditions prevalent in many inaccessible astrophysical environments, and provide important constraints for acceleration processes at such shocks.